2017
DOI: 10.1016/j.jalz.2017.06.1431
|View full text |Cite
|
Sign up to set email alerts
|

[P3–218]: Tau Plasma Levels in Subjective Cognitive Decline: Results From the Delcode Study

Abstract: Previous studies have demonstrated increased tau plasma levels in patients with Alzheimer's disease (AD) and mild cognitive impairment (MCI) due to AD. Much less is known whether increased tau plasma levels can already be detected in the pre-MCI stage of subjective cognitive decline (SCD). In the present study we measured tau plasma levels in 111 SCD patients and 134 age-and gendermatched cognitively healthy controls participating in the DZNE (German Center for Neurodegenerative Diseases) longitudinal study on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Overexpression of sTREM2 attenuated tau pathology and cognitive impairment in tau P301S transgenic mice. In addition, sTREM2 ( Laske et al, 2017 ; Hampel et al, 2018 ; Hansson et al, 2018 ; Lleo et al, 2019 ; Doecke et al, 2020 ; Aamodt et al, 2021 ; Clark et al, 2021 ; Simrén et al, 2021 ; Park et al, 2022 ; Zhang et al, 2022 ; Delaby et al, 2023 ; Dinoto et al, 2023 ; Pena-Bautista et al, 2023 ) is the smallest sTREM2 sequence that activates TG2 ( Zhang et al, 2023 ). This active peptide mimics the protective effects of sTREM2 both in vitro and in vivo .…”
Section: Alzheimer’s Disease-related Tau Pathological Changesmentioning
confidence: 99%
See 2 more Smart Citations
“…Overexpression of sTREM2 attenuated tau pathology and cognitive impairment in tau P301S transgenic mice. In addition, sTREM2 ( Laske et al, 2017 ; Hampel et al, 2018 ; Hansson et al, 2018 ; Lleo et al, 2019 ; Doecke et al, 2020 ; Aamodt et al, 2021 ; Clark et al, 2021 ; Simrén et al, 2021 ; Park et al, 2022 ; Zhang et al, 2022 ; Delaby et al, 2023 ; Dinoto et al, 2023 ; Pena-Bautista et al, 2023 ) is the smallest sTREM2 sequence that activates TG2 ( Zhang et al, 2023 ). This active peptide mimics the protective effects of sTREM2 both in vitro and in vivo .…”
Section: Alzheimer’s Disease-related Tau Pathological Changesmentioning
confidence: 99%
“…P-tau and t-tau in the CSF are connected to AD disease, with t-tau reflecting neurological damage and p-tau reflecting the extent of phosphorylated tau protein deposition in the brain. Increased concentrations of phosphorylated tau in the brain have been connected to a progressive reduction in cognitive function, and research has shown that p-tau concentrations in the CSF are 3.4 times larger in AD patients than in healthy controls, while elevated t-tau is not connected to the course of the disease ( Toledo et al, 2011 ; Laske et al, 2017 ; Müller et al, 2017 ; Clark et al, 2021 ; Frank et al, 2022 ). The assay for p-tau protein in the CSF focused on phosphorylation sites such as Thr181, which showed that the CSF in AD patients had significantly increased ( Delaby et al, 2023 ).…”
Section: Biomarkers Of Alzheimer’s Diseasementioning
confidence: 99%
See 1 more Smart Citation